Fatigue Crack Growth Investigation on a Maintenance Welding Repair Applied on a High Responsibility Airframe - Nascimento, Marcelino P. [UNESP]; Batista, Carolina C. [UNESP]; Sorrija, Bruno A. [UNESP]; Voorwald, Herman J. C. [UNESP]; Zhang, Z.; Skallerud, B.; Thaulow, C.; Ostby, E.; He, J. (Elsevier B.V., 2014)
Fatigue crack usually initiates at welded joints of structural elements. For a high-responsibility aeronautic component, called Motor-Cradle - critical to the flight safety -, successive weld repairs are carried out toward restoring the original condition of the aircraft and extending the in-service life of them. Motivated by the high fracture incidence on this particular component an extensive research program to evaluate the effects of maintenance weld repairs on the structural integrity, mechanical properties and microstructural changes has been developed. In this research-work, a maintenance weld repair procedures widely employed along the useful life of aircrafts, characterized by overlapping the weld bead by gas tungsten arc welding with filler metal was investigated. From the data obtained with fatigue crack growth laboratorial tests in base material (BM), heat affected zone (HAZ) and weld metal (WM) the effects of successive TIG welding repairs on the structural integrity of AISI 4130 aeronautical steel were analysed. After TIG welding and re-welding processes, specimens were prepared in accordance with ASTM 647 standard and fatigue tested with constant amplitude (R=0,1) at 10 Hz frequency and room temperature. The obtained results were associated to the micro hardness and microstructure variations, as well as to the residual stresses field generated by the successive weld cycles. Key-conclusion is that welding repair increase the fatigue crack growth resistance in the weld metal and in the HAZ. (C) 2014 Published by Elsevier Ltd.
Keywords: AISI 4130 aeronautic steel; TIG Welding; Welding Repair; Flight-Safety; HAZ